Sleepy and popular? The association between popularity, sleep duration, and insomnia in adolescents - Bauducco, Serena; Boersma, Katja; Gradisar, Michael (Frontiers in Sleep, 2024)
During adolescence, peers gain a central role and with the availability of technology, socializing can occur around the clock. Few studies have focused on the role of peers in adolescents' sleep using social network analyses. These analyses describe peer relationships and social positions in a defined context (e.g., school) based on friendship nominations. Adolescents who receive many nominations can be defined as "popular", which has been found to have its costs (i.e., shorter sleep duration) but also benefits (i.e., fewer insomnia symptoms). The aim of this study was to replicate and expand previous findings in a large Swedish sample of adolescents. The sample included 1394 adolescents (46% girls, Mage = 15.3, SD = .53, range 14-18) from 16 public schools. Adolescents reported on their weekly sleep duration, insomnia symptoms, anxiety, depression, alcohol use, demographics, and nominated up to three friends in school. We used R to calculate outgoing nominations and incoming nominations. Linear regressions were used to examine the association between popularity and sleep, controlling for confounding variables (demographics, emotional problems). Finally, we explored sex differences. Controlling for confounders, popular adolescents reported shorter sleep duration (B=-3.00; 95% CI [-5.77, -0.19]), and popular girls reported more insomnia symptoms (B = 0.36; 95% CI [.04,.68]). There were no significant associations found for boys. Popularity was linked to shorter sleep duration (up to -27 minutes for the most popular teens). Moreover, girls may pay a price for their popularity by experiencing more insomnia symptoms. Sex differences and potential mechanisms should be further explored.